Effects of stealth liposomal daunorubicin plus tamoxifen on the breast cancer and cancer stem cells - Jia Guo; Wan-Liang Lu (Frontiers Media S.A., 2010)
PURPOSE: The cancer stem cells play an important role in the invasion, metastasis and relapse of cancers as they are resistant to regular chemotherapy. In the present study, stealth liposomal daunorubicin plus tamoxifen was developed for eradicating breast cancer cells together with cancer stem cells. METHODS: Inhibitory effects were performed on the bulk human breast cancer cells (MCF-7), the sorted MCF-7 cancer stem-like cells (side population, SP), and the sorted MCF-7 cancer cells (NSP), respectively. Antitumor activity and TUNEL analysis were evaluated on the MCF-7 xenografts in nude mice. RESULTS: The encapsulation efficiencies of daunorubicin and tamoxifen were 95% and 90%, respectively. The mean particle size of the stealth liposomes was about 100 nm. Breast cancer stem cells were identified by the specific markers CD44+/CD24-, and isolated from bulk MCF-7 cells. When applying stealth liposomal daunorubicin plus tamoxifen, the inhibitory effects on both the breast cancer cells and the cancer stem cells were significantly increased in vitro, respectively. In the MCF-7 xenografts in mice, stealth liposomal daunorubicin plus tamoxifen showed the most favorable antitumor activity due to the passive targeting the tumor tissue and the synergistic effects in eliminating breast cancer cells and cancer stem cells. CONCLUSION: Stealth liposomal daunorubicin plus tamoxifen could have the potentials in eliminating both breast cancer cells and cancer stem cells.